Enhancing Students' Understanding of Aqeedah and Morality through Collaborative Learning at MI Al-Barokah Sentul - Safitri; Ahmad Sirthopil Laili (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) focuses on enhancing students' understanding of Aqeedah and Morality (Akidah Akhlak) through collaborative learning at MI Al-Barokah Sentul. Aqeedah and Morality are fundamental components of Islamic education that shape students' character, behavior, and worldview. However, traditional teaching methods often focus heavily on theoretical knowledge, leaving limited space for students to engage actively in the learning process. Collaborative learning, which encourages teamwork, discussion, and shared problem-solving, is introduced as an approach to foster deeper understanding and moral development in students. The research was conducted in two cycles with 30 students aged 10-12 years. During each cycle, collaborative activities such as group discussions, role-playing, and moral dilemma-solving tasks were implemented. These activities were designed to promote active engagement, encourage mutual learning, and deepen students' understanding of Islamic principles. Data was collected through observations, pre- and post-tests, and interviews with teachers and students. The results indicated a significant improvement in students' ability to articulate Islamic values, reflect on moral issues, and demonstrate positive behavior both inside and outside the classroom. The findings suggest that collaborative learning enhances not only academic understanding but also social skills, teamwork, and ethical reasoning among students. By involving students in cooperative learning experiences, they are encouraged to apply Aqeedah and Morality teachings in their daily lives. This study recommends the adoption of collaborative learning methods at MI Al-Barokah Sentul and other similar institutions to foster a more interactive, engaging, and holistic approach to teaching Islamic education.